The Functions of Taboo Words Spoken by the Characters in Ready or Not Movie - Santi, Ni Made Hyunika; Santika, I Dewa Ayu Devi Maharani (Journal of Language and Applied Linguistics, 2025)
One of human communication tools is language. Language can be divided into two types, formal and informal language. Taboo words are included in informal language because they can't be spoken in all situations or places. Taboo words are usually spoken by several people because they have their own functions when using them. The aim of this study is to find out the functions of taboo words that are used in the “Ready or Not” movie. This study used theory from Wardhaugh (2006: 239) to find out the functions of taboo words. The method being used in this study is a descriptive and qualitative method and observation technique to collect the data. In general, it is found three out of four functions of taboo words, those are to show contempt, to draw attention to oneself, and to be provocative.